Corporate Governance, Ownership and Control Structure and Financial Reporting Quality: A Comparative Study of South African and Nigerian Companies - Talabi, Amos Olatunbosun; Taib, Fauziah Md; Jalaludin, Dayana Binti (International Journal of Economics and Financial Issues, 2025)
This study investigates the influence of corporate governance, ownership and control structure on financial reporting quality (FRQ) in South African and Nigerian companies. The research employed three accrual-based models to analyze financial reporting quality (FRQ) for a sample of 150 companies selected based on market capitalization, including 75 firms from South Africa and 75 from Nigeria, from 2014 to 2023. The study found that corporate governance and the mix of ownership and control structures had a lesser influence on FRQ in Nigerian firms than in South African ones, which is useful information for regulators, investors, and policymakers. Based on the data, it seems that board size and foreign ownership are the factors that need regulatory attention to boost FRQ in both countries. Nigerian authorities are changing their position and calling for completely independent audit committees, citing the harmful effect of audit committee independence on FRQ. For the 1st time, the effects of ownership and control structure, corporate governance, and FRQ are being empirically compared in the context of two emerging nations.